GLIMPSE study: exploring the effectiveness of glimepiride and metformin combination therapy in newly diagnosed type 2 diabetes in India - Mayabhate, Mayur; Kapure, Nitin; Sharma, Akhilesh (International Journal of Advances in Medicine, 2025)
Background: Glimepiride and metformin FDC are still relevant in Indian settings as it promotes beta cell responsiveness, protects them from apoptosis and is highly cost-effective. The study aims to primarily understand the usage pattern of initial combination therapy of metformin and glimepiride in newly diagnosed T2DM patients in India. Methods: A retrospective multi-center cross-sectional study was conducted on 17994 newly diagnosed diabetic patients receiving an FDC of glimepiride and metformin. Baseline data included patient demographics and clinical examination findings, while glycemic parameters were measured at baseline and after 3 months of combination therapy. Key variables assessed included FDC strength, dosage frequency and the rationale for selecting the glimepiride-metformin combination. The clinician’s global assessment of therapy safety and effectiveness was also recorded. Results: The most frequently prescribed fixed-dose combinations (FDCs) were glimepiride 2 mg with metformin 500 mg (30.49%) and glimepiride 1 mg with metformin 500 mg (30.15%). Age was a significant determinant in the selection of combination therapy (p<0.001). At baseline, the mean hemoglobin A1c (HbA1c) level was 8.3%, which significantly improved to 7.3% following treatment for 3 months (p<0.001). Post-treatment FBG levels decreased from 172.8 mg/dl to 134.2 mg/dl, while postprandial blood glucose (PPBG) levels were reduced from 245.9 mg/dl to 187.8 mg/dl (both p<0.001). The majority of patients demonstrated either excellent or good outcomes based on the clinician’s global assessment of treatment effectiveness and safety. Conclusions: Metformin 500 mg with either 1 mg or 2 mg of glimepiride is the most frequently prescribed FDC in newly diagnosed T2DM patients as it offers mechanistic complementarity for insulin resistance and β-cell dysfunction, with good safety profile, along with cost effectiveness.